2013
DOI: 10.1186/1471-2334-13-27
|View full text |Cite
|
Sign up to set email alerts
|

Women experience a better long-term immune recovery and a better survival on HAART in Lao People’s Democratic Republic

Abstract: BackgroundIn April 2003, Médecins Sans Frontières launched an HIV/AIDS programme to provide free HAART to HIV-infected patients in Laos. Although HIV prevalence is estimated as low in this country, it has been increasing in the last years. This work reports the first results of an observational cohort study and it aims to identify the principal determinants of the CD4 cells evolution and to assess mortality among patients on HAART.MethodsWe performed a retrospective database analysis on patients initiated on H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 57 publications
1
16
1
Order By: Relevance
“…Several modeling strategies have been utilized to more rigorously describe CD4+ cell count recovery trajectories following ART initiation. Some have used linear mixed effects models[ 21 24 ], which have the drawback of enforcing a linear trend on every individual’s CD4+ cell count trajectory. Additional linear models include spline terms to account for changing slope over time[ 15 , 25 ], including hierarchical Bayesian change-point models[ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several modeling strategies have been utilized to more rigorously describe CD4+ cell count recovery trajectories following ART initiation. Some have used linear mixed effects models[ 21 24 ], which have the drawback of enforcing a linear trend on every individual’s CD4+ cell count trajectory. Additional linear models include spline terms to account for changing slope over time[ 15 , 25 ], including hierarchical Bayesian change-point models[ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“… 2011 ; Bastard et al . 2013 ). In Europe, the response to ART and mortality is similar for both sexes (Perez-Molina et al .…”
Section: Resultsmentioning
confidence: 99%
“…To date, several studies have reported that the strongest predictor of long-term CD4 response is baseline CD4, even among patients with long-term HIV RNA suppression [ 8 , 11 ]. In addition, studies have found that women [ 12 ] and patients initiating treatment at younger ages [ 13 ] show better CD4 response, whereas specific cART regimens have not been shown to significantly impact long-term immune response [ 14 ]. Our results corroborate these findings.…”
Section: Discussionmentioning
confidence: 99%